Food waste as a raw material for production of polyhydroxyalkanoates: State and prospects - A. P. Kuznetsova; R. I. Al-Shekhadat (Пищевые системы)
The growing problem of environmental pollution by plastic leads to the search not only for the most promising biodegradable polymer, but also for optimal raw materials for its production. Polyhydroxyalkanoates (PHA) — biodegradable polymers with physical and mechanical properties close to traditional plastics — are considered a potential solution to this problem. The production of PHA can be organized according to the principles of circular bioeconomy through biotechnological processing of secondary raw materials to produce a product with added value. However, an important component of the expansion of PHA production is the need to find the most promising secondary raw materials for its production. The PHA market in Russia and the global market have been analyzed, highlighting the demand in the packaging and food industries, biomedicine and agroindustry as the fundamental factor for the growth of PHA production. Bibliographic analysis using the PRISMA scheme and VOSviewer program allowed identifying three main directions of PHA research: search for optimal secondary raw materials among food waste, analysis of challenges in PHA production, and the ecological and economic effects of its implementation. Promising types of secondary raw materials have been revealed: vegetable oil production waste, fruit and vegetable processing waste, dairy whey, sugar and starch industry waste, spent coffee grounds and coffee oils extracted from them. Advantages and disadvantages of using secondary raw materials, options for improving their use in the production of PHA, and the main strains-producers were determined. To optimize the cost and processes of PHA production, further studies of food waste are required, aimed at developing approaches to increase the polymer yield, including through the use of secondary raw material preparation processes, and the search for the most productive strains synthesizing PHA.